2007
DOI: 10.1016/j.tafmec.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Lattice type of fracture model for concrete

Abstract: Concrete is usually described as a three-phase material, where matrix, aggregate and interface zones are distinguished. The beam lattice model has been applied widely by many investigators to simulate fracture processes in concrete. Due to the extremely large computational effort, however, the beam lattice model faces practical difficulties. In our investigation, a new lattice called generalized beam (GB) lattice is developed to reduce computational effort. Numerical experiments conducted on a panel subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 12 publications
0
65
0
Order By: Relevance
“…As for concrete, a remarkably large collection of papers are found that use an assembly of particles as a microstructure model; see, for instance, a list of related papers 14), 15) . The major concern is to treat microcracks of mortar in which aggregates are embedded 16),17), 18) .…”
Section: Literature Surveymentioning
confidence: 99%
“…As for concrete, a remarkably large collection of papers are found that use an assembly of particles as a microstructure model; see, for instance, a list of related papers 14), 15) . The major concern is to treat microcracks of mortar in which aggregates are embedded 16),17), 18) .…”
Section: Literature Surveymentioning
confidence: 99%
“…Here the discrete units are merely lattice sites (nodes). This type of models can be further classified into lattice spring [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and lattice beam [23][24][25][26] models according to the number of degrees of freedom per node and the mechanical properties of connecting elements. In a lattice three-dimensional cases and 0.33 for two-dimensional cases.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the above macro level models, the meso-level lattice-type model can simulate the complete failure process including nucleation and growth of micro cracks, formation, coalition and propagation of macro cracks until the final breakdown of the whole specimen [7][8][9]. Furthermore, this kind of models does not need any remeshing procedure or any smearing operation.…”
Section: Introductionmentioning
confidence: 99%
“…The GB lattice model proposed recently was employed to simulate tensile failures by adopting maximum tensile stress failure criterion at first [9]. Then it has been improved to investigate compressive failures by using the Mohr-Coulomb criterion [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation